2004
DOI: 10.1016/j.eupc.2004.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of ipratropium bromide and salbutamol on autonomic heart rate control

Abstract: Ipratropium inhalation may alter autonomic control of the heart rate in therapeutic doses during mild sympathetic stimulation in healthy subjects, while salbutamol does not show these effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Similarly, Dagnone and coworkers [45] did not find any significant changes in heart rate variability after inhalation of higher doses of albuterol (0.4 mg). The lack of monitoring respiratory rate [29, 31], or haemodynamic measurements such as cardiac output [29, 30, 45, 46] and blood pressure [28, 30] in these reports, however, may have prevented observation of important clinical sequels that may be associated with changes in HRV. Furthermore, both above‐mentioned studies may have neglected the acute effects of inhaled salbutamol within the first 45 min of application.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Similarly, Dagnone and coworkers [45] did not find any significant changes in heart rate variability after inhalation of higher doses of albuterol (0.4 mg). The lack of monitoring respiratory rate [29, 31], or haemodynamic measurements such as cardiac output [29, 30, 45, 46] and blood pressure [28, 30] in these reports, however, may have prevented observation of important clinical sequels that may be associated with changes in HRV. Furthermore, both above‐mentioned studies may have neglected the acute effects of inhaled salbutamol within the first 45 min of application.…”
Section: Discussionmentioning
confidence: 97%
“…Only few reports, however, have investigated the effects of inhaled short acting b2 agonists on HRV. Kaya et al [30] did not observe significant changes in HRV after inhalation of salbutamol (0.1 mg) in resting healthy probands. Similarly, Dagnone and coworkers [45] did not find any significant changes in heart rate variability after inhalation of higher doses of albuterol (0.4 mg).…”
Section: Figurementioning
confidence: 89%
See 2 more Smart Citations
“…In a study examining the effect of ipratropium on respiratory sinus arrhythmia, a non-specific indicator of parasympathetic modulation of heart rate, it has been shown to have no effect on asthmatic subjects (28). In our previous study we showed that inhalation of a single dose of ipratropium Mean RR 781±94 802±84 830±121 829±152 SDNN 48±25 53±26 55±19 52±11 RMSSD 34±27 30±25 35±23 30±16 HF 109±74 80±95 93±82 91±67 LF 205±108 181±109 140±55 147±64 HF nu 35±16 28±20 36±22 37±15 LF nu 65±16 72±20 64±22 63±15 LF/HF Mean RR 690±57 720±56 693±56 700±52 SDNN 55±19 56±31 59±31 63±34 RMSSD 28±15 28±15 32±23 38±39 HF 63±41 65±38 60±39 90±65 LF 242±93 281±83 268±52 244±125 HF nu 21±10 18±7 18±9 28±19 LF nu 79±10 82±7 82±9 72±19 LF/HF decreases parasympathetic modulation of heart rate in healthy men and this decrease in parasympathetic modulation of the heart occurs during mild exercise (29). In the current study, tiotropium is found not to affect autonomic tonus and modulation in healthy individuals during increased sympathetic and parasympathetic activity as it has no effect on time and frequency domain parameters of HRV by single dose administration during controlled breathing and light exercise.…”
Section: Discussionmentioning
confidence: 99%